A Universal Additive Strategy to Reshape Electrolyte Solvation Structure toward Reversible Zn Storage. Issue 15 (18th February 2022) - Li, Tian Chen; Lim, YewVon; Li, Xue Liang; Luo, Songzhu; Lin, Congjian; Fang, Daliang; Xia, Sunwen; Wang, Ye; Yang, Hui Ying
Abstract: The benefits of Zn, despite many of its performance advantages (e.g., high theoretical capacity and low redox potential), are compromised by severe side reactions and Zn dendrite growth in aqueous electrolytes, due to the coordinated H2 O within the Zn 2+ ‐solvation sheath and reactive free water in the bulk electrolyte. Unlike most efforts focused on costly super‐concentrated electrolytes and single additive species, a universal strategy is proposed to boost Zn reversibility in dilute electrolytes via adding carbonyl‐containing organic solvents. Based on experimental investigations and multiscale simulations, the representative electrolyte with a N ‐methyl‐2‐pyrrolidone polar additive is proved to assist in structural reshaping of Zn 2+ ‐solvation and stabilizing the hydrogen bond network of water. This synergy is instrumental in contributing to suppressed water‐induced parasitic reactions and dendrite formation, which enables high average coulombic efficiency of 99.7% over 1000 cycles in an Zn/Cu asymmetric cell, and an ultralong cycling lifespan of 2000 cycles with 99.4% capacity retention in a Zn/VS2 @SS full cell. Even with an elevated cathodic mass loading (up to 9.5 mg cm ‐2 ), the cycling stability is still maintained. The proposed strategy provides new insight into electrolyte additive design and sheds light on high‐performance Zn‐ion batteries. Abstract : Carbonyl‐containing organic solvents are employed as a kind of multifunctional additive for aqueous Zn‐ion batteries. Benefiting from their ability to reshape solvation structure and stabilize the hydrogen bond network of water, the parasitic reactions and dendrite formation are effectively inhibited. Consequently, the Zn batteries with a VS2 cathode and N ‐methyl‐2‐pyrrolidone‐added electrolyte can achieve highly reversible Zn storage over 2000 cycles.